Dampak Penggunaan Media Sosial (TikTok ) Terhadap Perkembangan Remaja - Dhilal Rizqullah; Auria Khairina; Badriani Saputri Saputri; Sabbila Nurcahyani (Biblio Couns : Jurnal Kajian Konseling dan Pendidikan, 2022)
Abstract : The purpose of this study was to obtain information about the impact of using social media (TikTok) on adolescent development. The research uses a case study method with a research approach using qualitative methods that are useful for obtaining information about the positive and negative impacts of using TikTok applications on adolescent development. In this study, 4 respondents were used in a high school in the city of Jambi. For confidentiality purposes, respondents were given the initials R1, R2, R3, and R4. The interviews were semi-structured and a list of questions was prepared for the interviews in order to be developed based on the relevant literature. The results of this study are that there are several positive and negative impacts on the use of the TikTok application, the positive impacts are being entertainment in spare time, getting new information, and being able to make shopping easier because of the online shopping feature. The negative impact of this TikTok application is that negative content is free to view, time is wasted due to watching useless content, and a lack of shame due to creating useless content.